Coronavirus Disease 2019 and Heart Failure: A Multiparametric Approach - Estefania Oliveros; Yevgeniy Brailovsky; Paul Scully; Evgenia Nikolou; Ronak Rajani; Julia Grapsa (Cardiac Failure Review, 2020)
Coronavirus disease 2019 (COVID-19) is a debilitating viral infection and, to date, 628,903 people have died from it, numbers that cannot yet be compared to the 50 million who died in the 1918 flu pandemic. As COVID-19 became better understood, cardiovascular manifestations associated with it were identified. This led to a complete healthcare restructuring with virtual clinics and changes to the triaging of critically ill patients. There are a lot of questions over how COVID-19 affects patients with heart failure (HF) as this condition is a leading cause of cardiovascular death. This review describes the cardiovascular implications of COVID-19 and new practices surrounding the use of telehealth to follow up and triage patients with HF. Current practices supported by medical societies, the role of angiotensin-converting enzyme inhibitors and, finally, a brief note regarding the management of advanced HF patients will also be discussed.